Interaction between somatic mutations and germline variants contributes to clinical heterogeneity in cancer. (2nd January 2020) - Musa, Julian; Grünewald, Thomas G. P.
ABSTRACT: Deciphering principles of inter-tumoral heterogeneity is crucial for refinement of precision oncology. We have recently demonstrated that 'oncogenic cooperation' between somatic mutations and regulatory germline variants can serve as a major cause for inter-tumoral heterogeneity, suggesting the requirement of integrating the regulatory genome into 'omics'-based precision oncology.